KEEFEKTIVAN PENGGUNAAN METODE THINK TALK WRITE DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA KELAS X SMK NEGERI 1 CIMAHI - Ernawati, Erna; Fauziah, Rizka; Mustika, Ika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on research on curiosity towards the use of think writing method in biographical text learning in class X. The formulation of the method can be used to talk about it. in learning biographical texts? Method for learning on biographical texts on class X students from SMK Negeri 1 Cimahi. The method used is the experimental method. This study uses the design of one group pretest-posttest. The research data is quantitative data that is analyzed through statistical analysis techniques. Class X TEI-B with a total of 27 students being used as research samples. The results of the initial test and the final test were compared with the average initial test 38 and the average final test 75. So, it can be concluded that the Think Talk Write method is effectively used in learning to write biographical texts.